Effects of uniaxial mechanical stress on drive current of 0.13 μm MOSFETs. - Wang, Y.G (IEEE Transactions on electron devices)
We study the effects of both external mechanical stress and intrinsic stress due to trench isolation on drive currents of 0.13 μm-node MOSFETs. The drive current, Idsat, of PMOS is enhanced by about 13% while that of NMOS is reduced by about 9% upon applying a uniaxial compressive stress along the channel of Lphysical=85 nm. The shifts in linear drive current, Idlin, are larger. By applying the external stress, we have simultaneously reproduced, for both PMOS and NMOS, the Idsat and Idlin shifts due to different gate-trench-isolation distances. We find that the shifts by the applied stress, ΔIdsat/Idsat0 and ΔIdlin/Idlin0, decrease with decreasing gate length. The change in total resistance, Δ(Vds/Idlin), is a linear function of gate length. Because of the mobility dependence on external stress, we have also been able to extract source-drain series resistance, Rsd, by simply bending the wafer.